Analysis of the Effectiveness of a Music Learning Information System for Early Childhood (Golden Age) using the Technology Adoption Model (TAM) - Safitri, Susan Juli; Rukhviyanti, Novi (Sinkron : jurnal dan penelitian teknik informatika, 2026)
Advances in information technology have brought significant changes to the education sector, including in the learning process for early childhood. The integration of information systems into learning activities is no longer limited to administrative functions but also serves as a learning medium capable of enhancing the effectiveness of the learning process. This study aims to analyze the effectiveness of implementing a music learning information system and to examine the relationship between the quality of the information system and student learning outcomes. The research analysis framework is based on the Technology Acceptance Model developed by Fred D. Davis to explain how perceptions of ease of use and information quality influence users’ adoption of technology. This study employs a quantitative approach with a correlational design. The study population consists of students in the New Primary music program at Yamaha Forte Music Bandung, totaling approximately 800 students. The research sample was determined using purposive sampling, calculated as rxy = (nΣXY − (ΣX)(ΣY)) / √[(nΣX² − (ΣX)²)(nΣY² − (ΣY)²)], with a total of 63 students who actively supported the use of the digital learning system. Data collection was conducted via a Likert-scale questionnaire measuring three primary dimensions of the information system: usability, information quality, and learning impact. Validity was assessed using Pearson’s Product-Moment correlation, while reliability was evaluated using Cronbach’s Alpha > 0.70. The research results indicate that the effectiveness of the music learning information system falls into the “very effective” category, with an average score of 81.3%. The usability dimension received the highest score of 87.5%, followed by information quality at 84.2%, and learning impact at 81.3%. The results of the correlation analysis indicate a positive relationship between the quality of the information system and student learning behavior, such as increased practice discipline, learning motivation, and self-confidence in music.